Improving Students' Reading Comprehension of Descriptive Text by Using Picture and Picture Technique at Junior High School - Nucke Ramadhani; Maria Yosephin Widarti Lestari; Indri Kustantinah (Lingua Franca, 2024)
This study aims to improve students’ reading skills using Picture and Picture Technique. The study used a quasi-experimental design with two classes of pre-test and post-test designs as the research design. The sample consisted of 23 VIII A students and 23 VIII B students from SMP Negeri 2 Tlogowungu in the academic year 2022/2023. The students were divided into two groups: experimental and control. A t-test was used to analyze the collected data. The analysis found that t-test had a greater value that the t table (t count = 10.017, t table = 2.074 at the level significant 5%). The reading skills of both groups has improved, yet there is a significant difference between the two. The average post-test learning result of the experimental class is 79.65, while the average control class is 61.39. As a result, it is possible to conclude that using the Picture and Picture Technique can improve students’ reading skills.